Climate responsive façade design: Exploring the performance limits of passive cooling strategies on various warm climates - Prieto Hoces, Alejandro Ignacio; Knaack, Ulrich; Auer, Thomas; Klein, Tillmann (A+BE | Architecture and the Built Environment, 2018)
Cooling demands of commercial buildings present a relevant challenge for a sustainable future. They account for over half of the overall energy needs for the operation of an average office building in warm climates, and this situation is expected to become more pressing due to increasing temperatures in cities worldwide. To tackle this issue, it is widely agreed that the application of passive strategies should be the first step in the design of energy efficient buildings, only using active equipment if it is truly necessary. Nonetheless, there is still further need for information regarding the potential limits derived from their application. This chapter explores the impact of selected passive cooling strategies in commercial buildings from warm climates, discussing their effectiveness in multiple scenarios and climate contexts. This task is carried out through the statistical analysis of results from documented research experiences, to define overall ranges and boundary conditions; and through software simulation of selected parameters to isolate their impact under a controlled experimental setup. General findings show that the mere inclusion of passive strategies is not enough to guarantee relevant savings. Their effectiveness is conditioned to both the harshness of a given climate and an adequate application of the strategies. Specific recommendations are discussed for the passive strategies considered in the evaluation, in order to optimise the overall performance of a given building in different climates.